Targeting the mTOR pathway using deforolimus in cancer therapy. (April 2009) - Mahalingam, Devalingam; Sankhala, Kamalesh; Mita, Alain; Giles, Francis J; Mita, Monica M
The mammalian target of rapamycin (mTOR) is an intracellular protein with a key role in cellular protein synthesis and energy balance that influences many aspects of cell growth and proliferation, including differentiation, cell-cycle progression, angiogenesis, protein degradation and apoptosis. mTOR can be activated by numerous oncogenic signals, such as growth factor activation through the EGF, IGF and VEGF receptors, mutation and silencing of the PTEN tumor suppressor gene, activating mutations in the PI3K catalytic subunit, Akt amplification and the Ras––Raf––MEK pathway. Once activated, the cellular functions of mTOR are achieved through its downstream targets, 4E-BP1 and p70S6K1. The mTOR pathway can be further regulated through a negative feedback loop, which may lead to resistance to specific inhibitors of mTOR. This review will outline the mTOR signaling pathway, which is often activated in cancers and account for tumor proliferation and growth, highlight the rationale in targeting mTOR with a focus on the preclinical and clinical development of one of these inhibitors, deforolimus (AP23573, MK-8669), and discuss potential benefit and barriers to these agents being introduced in the clinic.